Conductive silver paste with ultralow silver content and preparation and application thereof
By using a mixture of silver powder with low tap density and high tap density in the silver paste, combined with specific resins and solvents, adding thixotropic agents and adhesion promoters, ultra-low silver content conductive silver paste is prepared, which solves the problems of large resistance, poor dispersion and poor weather resistance in the prior art, and achieves fast drying performance, good adhesion and hardness, and shows good weather resistance in high temperature and high humidity environments.
Patent Information
- Application Number
- CN202411980838.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-25
AI Technical Summary
The existing ultra-low silver content silver paste has large line resistance, poor dispersion, poor weather resistance on PET films, and is prone to oxidation in high temperature and high humidity environments, resulting in failure of the silver layer.
By using a mixture of silver powder with low tap density and high tap density in the silver paste, combined with ternary chlorine acetic acid resin and divalent acid ester as solvent, and adding thixotropic agent and adhesion promoter, a conductive silver paste with a silver powder content of ≤30% was prepared, and fineness of less than 10 μm and viscosity of 10 to 15 Pa·s was achieved by grinding treatment.
The fast drying performance, good adhesion and hardness of conductive silver paste are achieved, and good weather resistance is shown in high temperature and high humidity environments, reducing production costs.
Smart Images

Figure CN119889766A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of conductive silver paste, and in particular to a conductive silver paste with ultra-low silver content and a preparation method and application thereof. Background Art
[0002] With the development of flexible electronic technology, it has become a common method to print circuits on flexible materials such as PET film using silver paste. Silver paste has good electrical properties due to the conductivity of silver. By adjusting the silver content, it can match the needs of different industries and is widely used in various industries such as automobiles, home appliances and medical care. Silver is a precious metal and is expensive. Its price has continued to rise in recent years. Therefore, reducing the silver powder content in the silver paste is a direct way to reduce the application cost. The current problems of ultra-low silver content silver paste mainly focus on: low silver content paste has high resistance, poor paste dispersibility, poor weather resistance and other problems. Due to the extremely low silver powder content, the circuit resistance on the PET film material is large and cannot meet the requirements; compared with high silver content paste, the resin and solvent components in the low silver content paste are higher, which is prone to segregation and unevenness; the silver paste on the PET film material is generally dried at low temperature, and is easily oxidized in a high temperature and high humidity environment, resulting in failure of the silver layer circuit. Summary of the invention
[0003] In order to solve the above problems, the purpose of the present invention is to provide a conductive silver paste with ultra-low silver content and its preparation and application. The ultra-low content conductive silver paste provided by the present invention comprises the following components in percentage by mass: silver powder ≤ 30%, polymer resin 8% to 12%, solvent 50% to 60%, thixotropic agent 0.1 to 1%, adhesion promoter 0.1 to 1%; wherein the sum of the mass percentages of the components is 100%. Compared with the existing conductive silver paste, the conductive silver paste provided by the present invention has a lower silver content, which can reduce costs and save resources; the conductive silver paste also has quick drying performance, good adhesion and hardness, and good high temperature and high humidity resistance.
[0004] The purpose of the present invention can be achieved by the following technical solutions:
[0005] The first object of the present invention is to provide an ultra-low content conductive silver paste, comprising the following components in percentage by mass:
[0006] Silver powder ≤30%, polymer resin 8%~12%, solvent 50%~60%, thixotropic agent 0.1~1%, adhesion promoter 0.1~1%;
[0007] The sum of the mass percentages of the various components is 100%.
[0008] In one embodiment of the present invention, the silver powder has a tap density of 1.5 to 1.9 g / cm 3Low tap density flake silver powder and tap density of 2.2-2.7 g / cm 3 A mixture of high tap density flake silver powder.
[0009] In one embodiment of the present invention, the mass percentage of the low tap density flaky silver powder is 15 to 25%, and the mass percentage of the low tap density flaky silver powder is 5 to 10%.
[0010] In one embodiment of the present invention, the polymer resin is one or more of ternary chloroacetic acid resin VYHH, hydroxyl-modified chloroacetic acid resin VAGH, and carboxylic acid-modified chloroacetic acid resin VMCH.
[0011] In one embodiment of the present invention, the solvent is selected from one or more of dibasic acid esters or propylene glycol methyl ether acetate.
[0012] In one embodiment of the present invention, the thixotropic agent is selected from one or more of polyurea thixotropic agent BYK-410, organic bentonite BP-186 or fumed silica HDK-V15.
[0013] In one embodiment of the present invention, the adhesion promoter is selected from one or more of adhesion promoter AKN-6008, adhesion promoter AKN-6015, and adhesion promoter AKN-6088.
[0014] A second object of the present invention is to provide a method for preparing an ultra-low content conductive silver paste, comprising the following steps:
[0015] (S1) adding a polymer resin into a solvent, heating and mixing to obtain a resin carrier;
[0016] (S2) mixing silver powder, thixotropic agent, adhesion promoter, and the resin carrier prepared in step (S1) to obtain a mixed slurry;
[0017] (S3) Grinding the mixed slurry prepared in step (S2) to obtain the ultra-low silver content conductive silver paste.
[0018] In one embodiment of the present invention, in step (S1), the temperature during heating is 70 to 90°C;
[0019] In step (S3), the fineness of the ultra-low silver content conductive silver paste is less than 10 μm, and the viscosity is 10 to 15 Pa·s.
[0020] The third object of the present invention is to provide an application of ultra-low content conductive silver paste in the preparation of PET film.
[0021] Compared with the prior art, the present invention has the following beneficial effects:
[0022] The invention combines a plurality of silver powders with different bulk density and tap density, thereby reducing the content of silver powder and ensuring the electrical properties of the conductive silver paste, thereby reducing the production cost; by mixing two chloroacetic resins, the quick-drying property of the silver paste is ensured and the adhesion of the silver paste is improved; by introducing an adhesion promoter, the adhesion of the silver paste on the surfaces of different materials is further enhanced; by introducing a thixotropic agent, the screen printing property, storage stability and ease of use of the paste can be improved; in addition, the paste has good high temperature and high humidity resistance. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 The actual pictures of PET film before and after high temperature and high humidity test; Figure 1 A is embodiment 3; Figure 1 B is comparative example 3. DETAILED DESCRIPTION
[0024] The present invention is described in detail below with reference to the accompanying drawings and specific embodiments.
[0025] In the following examples, unless otherwise specified, all reagents used are commercially available reagents, and all monitoring means and methods used are conventional detection means and methods in the art.
[0026] Example 1
[0027] This embodiment provides a method for preparing a conductive silver paste with ultra-low silver content, comprising the following steps:
[0028] (S1) adding 25 g of chloroacetic acid resin VYHH to 75 g of diformic acid ester, heating and dissolving at 80° C., and stirring to obtain a chloroacetic acid resin VYHH carrier;
[0029] Add 25g of chloroacetic acid resin VAGH to 75g of diformic acid ester, heat and dissolve at 80°C, and stir evenly to obtain chloroacetic acid resin VAGH carrier;
[0030] (S2) 2 g of isophorone, 14 g of diformate, 8 g of propylene glycol methyl ether acetate, and 9 g of high-tap silver powder (tap density of 1.5 g / cm 3 )、21g low tap silver powder (tap density is 2.5g / cm 3 ), 0.5 g bentonite BP-186, 0.5 g adhesion promoter AKN-6008, 25 g chloroacetic acid resin VYHH carrier prepared in step (S1) and 20 g chloroacetic acid resin VAGH carrier are placed in a stirrer and stirred to obtain a mixed slurry;
[0031] (S3) placing the mixed slurry prepared in step (S2) on a three-roll grinder for grinding, controlling the fineness to be less than 10 μm and the viscosity to be 10 to 15 Pa·s, thereby preparing the ultra-low silver content conductive silver paste.
[0032] Furthermore, the ultra-low silver content conductive silver paste prepared in this embodiment was printed on a PET film using a screen printer to conduct an industry standard test.
[0033] The test performance is as follows:
[0034] The conductive silver paste prepared in this embodiment has a square resistance of 24.2 mΩ / □ / mil after drying at 150°C for 2 minutes, can be dried quickly, and has a resistance close to that of a paste with a silver content of 40% at the same thickness (square resistance of 24 mΩ / □ / mil after drying at 150°C for 5 minutes), a hardness of ≥3H, and good adhesion (a small amount of powder falling off in a 3M tape peeling test); the screen printing process is smooth and free of bubbles, the light-shielding property is good after printing, and there are no pinholes after drying.
[0035] Example 2
[0036] This embodiment provides a method for preparing a conductive silver paste with ultra-low silver content, comprising the following steps:
[0037] (S1) adding 25 g of chloroacetic acid resin VYHH to 75 g of dibasic acid ester, heating and dissolving at 80° C., and stirring to obtain a chloroacetic acid resin VYHH carrier;
[0038] Add 25g of chloroacetic acid resin VAGH to 75g of divalent acid ester, heat and dissolve at 80°C, and stir evenly to obtain chloroacetic acid resin VAGH carrier;
[0039] (S2) 2 g of isophorone, 14 g of diformate, 8 g of propylene glycol methyl ether, and 7 g of high-tap silver powder (tap density 2.5 g / cm 3 )、23g low tap silver powder (tap density 1.5g / cm 3 ), 0.5 g of bentonite BP-186, 0.5 g of plastic film adhesion promoter AKN-6008, 25 g of the chloroacetic acid resin VYHH carrier prepared in step (S1), and 20 g of the chloroacetic acid resin VAGH carrier are placed in a stirrer and stirred to obtain a mixed slurry;
[0040] (S3) placing the mixed slurry prepared in step (S2) on a three-roll grinder for grinding, controlling the fineness to be less than 10 μm and the viscosity to be 10 to 15 Pa·s, thereby preparing the ultra-low silver content conductive silver paste.
[0041] Furthermore, the ultra-low silver content conductive silver paste prepared in this embodiment was printed on a PET film using a screen printer to conduct an industry standard test.
[0042] The test performance is as follows:
[0043] The conductive silver paste prepared in this embodiment has a square resistance of 18.4 mΩ / □ / mil after drying at 150°C for 2 minutes, can be dried quickly, has a resistance lower than the paste with 40% silver content (square resistance of 24 mΩ / □ / mil after drying at 150°C for 5 minutes), has a hardness of ≥3H, and has good adhesion (no peeling in the 3M tape peeling test). The screen printing process is smooth and free of bubbles, has good light-shielding properties after printing, and has no pinholes after drying.
[0044] Example 3
[0045] This embodiment provides a method for preparing a conductive silver paste with ultra-low silver content, comprising the following steps:
[0046] (S1) adding 25 g of chloroacetic acid resin VYHH to 75 g of diformic acid ester, heating and dissolving at 80° C., and stirring to obtain a chloroacetic acid resin VYHH carrier;
[0047] Add 25g of chloroacetic acid resin VMCH to 75g of diformic acid ester, heat and dissolve at 80°C, and stir evenly to obtain chloroacetic acid resin VMCH carrier;
[0048] (S2) 2 g of isophorone, 14 g of dibasic acid ester, 8 g of propylene glycol methyl ether acetate, and 9 g of high-tap silver powder (tap density 2.5 g / cm 3 )、21g low tap silver powder (tap density 1.5g / cm 3 ), 0.5 g of bentonite, 0.5 g of a plastic film adhesion promoter, 25 g of the chlorovinyl resin VYHH carrier prepared in step (S1), and 20 g of the chlorovinyl resin VMCH carrier are placed in a stirrer and stirred to obtain a mixed slurry;
[0049] (S3) placing the mixed slurry prepared in step (S2) on a three-roll grinder for grinding, controlling the fineness to be less than 10 μm and the viscosity to be 10 to 15 Pa·s, thereby preparing the ultra-low silver content conductive silver paste.
[0050] Furthermore, the ultra-low silver content conductive silver paste prepared in this embodiment was printed on a PET film using a screen printer to conduct an industry standard test.
[0051] The test performance is as follows:
[0052] The conductive silver paste prepared in this embodiment has a square resistance of 23.9mΩ / □ / mil after drying for 5 minutes at 150°C, which is close to the paste with 40% silver content (24mΩ / □ / mil), hardness ≥3H, and good adhesion (no peeling in the 3M tape peeling test). The screen printing process is smooth and free of bubbles, the light-shielding property is good after printing, and there are no pinholes after drying. After high temperature and high humidity testing (temperature 85°C, humidity 85%) for 24 hours, there is no discoloration on the circuit surface, such as Figure 1 As shown in A, the resistance change rate before and after is less than 10%.
[0053] Comparative Example 1
[0054] This comparative example provides a method for preparing an ultra-low silver content conductive silver paste, comprising the following steps:
[0055] (S1) adding 25 g of chloroacetic acid resin VYHH to 75 g of diformic acid ester, heating and dissolving at 80° C., and stirring to obtain a chloroacetic acid resin VYHH carrier;
[0056] Add 25g of chloroacetic acid resin VAGH to 75g of diformic acid ester, heat and dissolve at 80°C, and stir evenly to obtain chloroacetic acid resin VAGH carrier;
[0057] (S2) 2 g of isophorone, 14 g of diformate, 8 g of propylene glycol methyl ether acetate, and 30 g of high-tap silver powder (tap density 2.5 g / cm 3 ), 0.5 g of bentonite BP-186, 0.5 g of plastic film adhesion promoter AKN-6008, 25 g of the chloroacetic acid resin VYHH carrier prepared in step (S1), and 20 g of the chloroacetic acid resin VAGH carrier are placed in a stirrer and stirred to obtain a mixed slurry;
[0058] (S3) placing the mixed slurry prepared in step (S2) on a three-roll grinder for grinding, controlling the fineness to be less than 10 μm and the viscosity to be 10 to 15 Pa·s, thereby preparing the ultra-low silver content conductive silver paste.
[0059] Furthermore, the ultra-low silver content conductive silver paste prepared in this comparative example was printed on a PET film using a screen printer to conduct an industry standard test.
[0060] The test performance is as follows:
[0061] The conductive silver paste prepared in this comparative example has a square resistance of 30.2 mΩ / □ / mil after drying for 2 min at 150°C, which is much greater than that of Example 1 (24.2 mΩ / □ / mil) and Example 2 (18.4 mΩ / □ / mil), a hardness of ≥3H, and good adhesion (whether there is powder loss in the 3M tape peeling test); the screen printing process is smooth and free of bubbles, the light-shielding property is good after printing, and there are no pinholes after drying.
[0062] Comparative Example 2
[0063] This comparative example provides a method for preparing an ultra-low silver content conductive silver paste, comprising the following steps:
[0064] (S1) adding 25 g of chloroacetic acid resin VYHH to 75 g of diformic acid ester, heating and dissolving at 80° C., and stirring to obtain a chloroacetic acid resin VYHH carrier;
[0065] Add 25g of chloroacetic acid resin VAGH to 75g of diformic acid ester, heat and dissolve at 80°C, and stir evenly to obtain chloroacetic acid resin VAGH carrier;
[0066] (S2) 2 g of isophorone, 14 g of diformate, 8 g of propylene glycol methyl ether, and 30 g of low-tap silver powder (tap density 1.5 g / cm 3 ), 0.5 g of bentonite BP-186, 0.5 g of plastic film adhesion promoter AKN-6008, 25 g of the chloroacetic acid resin VYHH carrier prepared in step (S1), and 20 g of the chloroacetic acid resin VAGH carrier are placed in a stirrer and stirred to obtain a mixed slurry;
[0067] (S3) placing the mixed slurry prepared in step (S2) on a three-roll grinder for grinding, controlling the fineness to be less than 10 μm and the viscosity to be 10 to 15 Pa·s, thereby preparing the ultra-low silver content conductive silver paste.
[0068] Furthermore, the ultra-low silver content conductive silver paste prepared in this comparative example was printed on a PET film using a screen printer to conduct an industry standard test.
[0069] The test performance is as follows:
[0070] The conductive silver paste prepared in this comparative example has a square resistance of 26.5 mΩ / □ / mil after drying for 2 min at 150°C, which is greater than that of Example 1 (24.2 mΩ / □ / mil) and Example 2 (18.4 mΩ / □ / mil). At the same time, the hardness is ≤2H, the adhesion is poor (whether there is powder loss in the 3M tape peeling test), and a large amount of silver layer falls off.
[0071] Comparative Example 3
[0072] This embodiment provides a method for preparing a conductive silver paste with ultra-low silver content, comprising the following steps:
[0073] (S1) adding 25 g of chloroacetic acid resin VYHH to 75 g of dibasic acid ester, heating and dissolving at 80° C., and stirring to obtain a chloroacetic acid resin VYHH carrier;
[0074] Add 25g of chloroacetic acid resin VAGH to 75g of diformic acid ester, heat and dissolve at 80°C, and stir evenly to obtain chloroacetic acid resin VAGH carrier;
[0075] (S2) 2 g of isophorone, 14 g of diformate, 8 g of propylene glycol methyl ether, and 7 g of high-tap silver powder (tap density 2.5 g / cm 3 )、23g low tap silver powder (tap density 1.5g / cm 3 ), 0.5 g of bentonite BP-186, 0.5 g of plastic film adhesion promoter AKN-6008, 25 g of the chloroacetic acid resin VYHH carrier prepared in step (S1), and 20 g of the chloroacetic acid resin VAGH carrier are placed in a stirrer and stirred to obtain a mixed slurry;
[0076] (S3) placing the mixed slurry prepared in step (S2) on a three-roll grinder for grinding, controlling the fineness to be less than 10 μm and the viscosity to be 10 to 15 Pa·s, thereby preparing the ultra-low silver content conductive silver paste.
[0077] Furthermore, the ultra-low silver content conductive silver paste prepared in this embodiment was printed on a PET film using a screen printer to conduct an industry standard test.
[0078] The test performance is as follows:
[0079] The conductive silver paste prepared in this embodiment has a square resistance of 28.4 mΩ / □ / mil after drying for 2 minutes at 150°C, a hardness of ≥3H, and good adhesion (no peeling in the 3M tape peeling test). The screen printing process is smooth and free of bubbles, the light shielding is good after printing, and there are no pinholes after drying. After high temperature and high humidity testing (temperature 85°C, humidity 85%) for 24 hours, a large number of discoloration spots appear on the circuit surface, such as Figure 1 As shown in B, the resistance change rate before and after is greater than 20%.
[0080] The above description of the embodiments is to facilitate the understanding and use of the invention by those skilled in the art. It is obvious that those skilled in the art can easily make various modifications to these embodiments and apply the general principles described herein to other embodiments without creative work. Therefore, the present invention is not limited to the above embodiments, and improvements and modifications made by those skilled in the art based on the explanation of the present invention without departing from the scope of the present invention should be within the scope of protection of the present invention.
Claims
1. An ultra-low content conductive silver paste, characterized in that: The following components are included in mass percentage: Silver powder ≤30%, polymer resin 8%~12%, solvent 50%~60%, thixotropic agent 0.1~1%, adhesion promoter 0.1~1%; The sum of the mass percentages of the various components is 100%.
2. The ultra-low content conductive silver paste according to claim 1, characterized in that: The silver powder has a tap density of 1.5 to 1.9 g / cm 3 Low tap density flake silver powder and tap density of 2.2-2.7 g / cm 3 A mixture of high tap density flake silver powder.
3. The ultra-low content conductive silver paste according to claim 2, characterized in that: The mass percentage of the low tap density flaky silver powder is 15-25%, and the mass percentage of the low tap density flaky silver powder is 5-10%.
4. The ultra-low content conductive silver paste according to claim 1, characterized in that: The polymer resin is one or more of ternary chloroacetic acid resin VYHH, hydroxyl-modified chloroacetic acid resin VAGH, and carboxylic acid-modified chloroacetic acid resin VMCH.
5. The ultra-low content conductive silver paste according to claim 1, characterized in that: The solvent is selected from one or more of dibasic acid esters or propylene glycol methyl ether acetate.
6. The ultra-low content conductive silver paste according to claim 1, characterized in that: The thixotropic agent is selected from one or more of polyurea thixotropic agent BYK-410, organic bentonite BP-186 or fumed silica HDK-V15.
7. The ultra-low content conductive silver paste according to claim 1, characterized in that: The adhesion promoter is selected from one or more of adhesion promoter AKN-6008, adhesion promoter AKN-6015, and adhesion promoter AKN-6088.
8. A method for preparing an ultra-low content conductive silver paste as claimed in any one of claims 1 to 7, characterized in that: The following steps are involved: (S1) adding a polymer resin into a solvent, heating and mixing to obtain a resin carrier; (S2) mixing silver powder, thixotropic agent, adhesion promoter, and the resin carrier prepared in step (S1) to obtain a mixed slurry; (S3) Grinding the mixed slurry prepared in step (S2) to obtain the ultra-low silver content conductive silver paste.
9. The method for preparing ultra-low content conductive silver paste according to claim 8, characterized in that: In step (S1), the temperature during heating is 70 to 90°C; In step (S3), the fineness of the ultra-low silver content conductive silver paste is less than 10 μm, and the viscosity is 10 to 15 Pa·s.
10. Use of the ultra-low content conductive silver paste according to any one of claims 1 to 7 in the preparation of PET film.